PPI Program For Treating Antimicrobial Resistance - Anggrieni Wisni (Syntax Corporation Indonesia, 2022)
The problem of antimicrobial resistance is a big thing in health services both in hospitals and in the community. The purpose of organizing the PPI program is to be able to find findings and reduce the possibility of infections that occur in groups of patients, employees, medical and non-medical personnel, permanent staff, part-time staff and volunteers, students and other hospital consumers